Critical Reflections on Australian Public Policy Selected Essays - Wanna, John (ANU Press, 2009)
This collection of 'critical reflections' on Australian public policy offers a valuable contribution to public discussion of important political and policy issues facing our nation and society. These essays are important not only because of the reputation and position of the various contributors, but because they are incredibly 'content rich' and brimming with new ideas.